2017
DOI: 10.1016/j.ekir.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Genotype–Phenotype Correlation in Female X-Linked Alport Syndrome

Abstract: IntroductionX-linked Alport syndrome (XLAS) is a hereditary disease characterized by progressive nephritis, hearing loss, and ocular abnormalities. Affected male patients usually progress to end-stage renal disease in early or middle adulthood, and disease severity is strongly correlated with genotype. However, the clinical course in female patients has rarely been reported.MethodsWe conducted a retrospective analysis of females with genetically proven XLAS (n = 275) and their affected female family members (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 13 publications
2
73
1
Order By: Relevance
“…In total, 441 families were included in this study. Among them, 25 families with ADAS (Kamiyoshi et al, ), 24 families with ARAS (Oka et al, ), and 215 families with XLAS (Hashimura et al, ) (Yamamura et al, ) (Horinouchi et al, ) have already been reported by our group.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In total, 441 families were included in this study. Among them, 25 families with ADAS (Kamiyoshi et al, ), 24 families with ARAS (Oka et al, ), and 215 families with XLAS (Hashimura et al, ) (Yamamura et al, ) (Horinouchi et al, ) have already been reported by our group.…”
Section: Resultsmentioning
confidence: 76%
“…Alport syndrome (AS) is a hereditary disease caused by mutations in collagen type‐IV alpha chain genes (specifically, COL4A3 / COL4A4 / COL4A5 , OMIM: 12007, 120131, 303630), which is characterized by progressive renal involvement, hearing loss, and ocular abnormalities (Kashtan & Michael, ). Mutations in COL4A5 , encoding the collagen type IV α5 chain, are responsible for X‐linked AS (XLAS), which is usually more severe in men than women (Jais et al, , ; Yamamura et al, ). Mutations in COL4A3 and COL4A4 , encoding the collagen type IV α3 and α4 chains, are responsible for autosomal AS.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from the natural history of female patients with XLAS. It has been reported that hematuria, usually microscopic, presented in 96% of females with XLAS and proteinuria developed in 72.6-75% [8,25]. Especially a median renal survival age of 65.0 years in females with XLAS was reported [8].…”
Section: Gene Analysismentioning
confidence: 99%
“…Eighty-five percent of families have X-linked Alport syndrome (XLAS) with mutations in COL4A5 gene [6,7]. It is well known that male patients with XLAS, who are hemizygous for mutations in COL4A5 gene, are severely affected [8,9]. All of the males have microscopic hematuria and 90% of them progress to end-stage renal disease (ESRD) before age 40 years [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Males with X-linked Alport syndrome (XLAS) are affected more severely than females (Massella et al, 2003;Raju, Cimbaluk, & Korbet, 2013;Savige, Colville, et al, 2016;Savige, Storey et al, 2016). Ninety percent of males with XLAS progress to end-stage renal disease (ESRD) by age 40, but only about 20% of females with XLAS develop renal failure by age 60 (Jais et al, 2000(Jais et al, , 2003Naito, Kawai, Nomura, Sado, & Osawa, 1996;Wang, Ding, Guo, & Yang, 2002;Wang et al, 2012;Yamamura et al, 2017). Fifteen percent of individuals with Alport syndrome are autosomal recessive inherited caused by homozygous or compound heterozygous mutations from both alleles of either COL4A3 or COL4A4 genes (Storey, Savige, Sivakumar, Abbs, & Flinter, 2013;Wang et al, 2014;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%